How Many Ways of Thinking Literature across Continents?. Issue 3 (December 2017) - Yao, Steven
Abstract : Taking as its prompt Ranjan Ghosh and J. Hillis Miller's Thinking Literature across Continents (Duke University Press, 2016), this article explores some aspects of the ethics of 'sahitya' / literature in the current world historical moment of global capitalism, relating that in the first instance to the practice of reading, studying, and teaching literature across different international and institutional contexts. It then addresses some of the questions surrounding issues arising from each term (particularly across ) in Ghosh and Miller's title, before devoting itself to a study of the transpacific: 'a transformative space of encounter both in response to and as a part of the global spread of modernity and the associated processes of technological and economic globalisation'. The transpacific appears as a specific and subversive 'thalassapolitan' case that both upholds and undercuts the arguments presented by Ghosh and Miller. This is amplified by a close reading of the Japanese writer of 'Merican-Jap' [ meriken jappu ] stories Jōji Tani: specifically, his story 'The Shanghaied Man', which emerges as a powerful allegorical representation – and critique – of aspects discussed in Thinking Literature across Continents, but also within the study of world and postcolonial literature in the present moment.